PENGARUH KONSEP BOBATH TERHADAP PENINGKATAN KEMAMPUAN FUNGSIONAL PASIEN PEREMPUAN DAN LAKI-LAKI PASCA STROKE DI RSU HAJI MEDAN - Sari, Putri Harum; Susilo, Trisno; Vera, Yeni (Pusat Studi Gender dan Anak, 2024)
Stroke will result in impaired functional ability and decreased quality of life. The Bobath concept aims to optimize function by improving postural control and selective movement through facilitation to improve functional ability. Several studies have shown the effectiveness of the Bobath concept as a rehabilitation program for post-stroke patients. This study aims to see the effect of the Bobath concept on improving post-stroke functional abilities. This study is a quasi-experimental with a one group pretest and posttest design. The functional ability of patients was measured using the Barthel Index before and after training. There was 1 treatment group without a control group, with a sample in this study of 18 respondents. The results showed that there were differences in measurement results using the Barthel Index before and after exercise with the Bobath Concept. Based on the results of the Wilcoxon Signed Rank Test calculation, the Z value obtained is - 3.162 with a p value (Asymp. Sig 2 tailed) of 0.002. This shows that there is a positive effect of the Bobath concept on improving the functional abilities of post-stroke patients at RSU Haji Medan, North Sumatra Province. Based on the results of this study, it is recommended that the Bobath concept be applied more frequently in rehabilitation programs for post-stroke patients, given its effectiveness in improving functional abilities. Further training for health workers is also needed to better understand and master the techniques in the Bobath approach.